Pembekalan Program Anti Korupsi Kepada Penerima Dana Gempa di Kenagarian Pakandangan, Kabupaten Padang Parimaan - Shinta Agustina; Elwi Danil; Yoserwan Yoserwan; Iwan Kurniawan; Edita Elda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2016)
Corruption has penetrated into all aspects of people’s life in Indonesia as nation and state, as well as to the communities in rural areas. Corruption occurs in all fields, such as politics, education, religion, and social affairs, including in the distribution of earthquake relief fund in West Sumatra. One of the Corruption Court’s decisions in Padang, has sentenced several chairmans of Community Group, which has been formed to coordinate the distribution of the fund, due to corruption. Corruption by the low level people in the countryside is very different from the the corruption’s shape by state officials. They often happened due to lack of information that it is a form of corruption rather than habbits in community practices. This fact is precisely found in the distribution of reliefs fund in Kenagarian Pakandangan, the province of Padang Pariaman. Debriefing Program conducted by the lecturers from the faculty of law, Andalas University, brings substantial benefits to citizens in Pakandangan, in understanding the shape and behaviors of corruption. In general, people want this program to be continued in the following years, and given not only to adult but also to students, ranging from elementary to higher education.